THE IMPACT OF TAURINE AND CAFFEINE IN ENERGY DRINKS ON THE DEVELOPMENT OF DENTAL CARIES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article examines the effects of taurine and caffeine—key components of energy drinks—on the development of dental caries and enamel erosion. Findings from small-scale scientific investigations indicate that the low pH levels, high sugar content, and alterations in fluid balance caused by energy drinks weaken tooth enamel, reduce salivary secretion, and create a favorable environment for bacterial growth. Moreover, some laboratory and clinical studies suggest that the addition of green tea extract to energy drinks may reduce enamel erosion, indicating its potential use as a protective strategy. The article emphasizes that excessive consumption of energy drinks among young people, students, and athletes significantly increases the risk of dental problems. Preventive strategies include limiting consumption, substituting energy drinks with water or milk, rinsing the mouth after intake, and undergoing regular dental checkups. Additionally, healthcare professionals and dentists should raise public awareness about the harmful effects of these beverages. The article provides a comprehensive overview of the impact of energy drinks on oral health, risk factors, and preventive measures.